Changing the subject:A community of philosophical inquiry in prisons - Anderson, Charles (2020)
This article reports on part of a project that introduced philosophy programmes to a number of Scottish prisons. It centres on the deployment within these prisons of McCall’s (1991) Community of Philosophical Inquiry (CoPI). It provides a rationale for, and analyses the participation structure, of CoPI, setting out how its communicative constraints and demands provided prisoners with novel means of reasoning and engaging in dialogue with others and with oneself. In interviews conducted with a sample of participants, they described how the critical listening to, and reasoning with, each other in CoPI tutorials had allowed them to develop greater self-awareness and a more reflexive understanding of their own thinking and actions. Findings are framed within sociocultural theorising on literacies, learning and identity. Drawing on Holland, Lachicotte, Skinner & Cain (1998) account of identity and agency, the authors show how CoPI afforded participants a new positionality and discursive practices. (DIPF/Orig.